O papel dos sistemas de custos nas pequenas e médias empresas como ferramenta de gestão empresarial, elemento essencial na busca da competitividade - Azevedo, Hélio Moreira de (2004)
NEVES, Hélio Ramiro Marques. Os fluxos internacionais de capitais para investimentos em portfólio no mercado financeiro doméstico: uma análise do caso brasileiro de 1994 a 2000. 2004. f. Dissertação (Mestrado em Gestão Empresarial) ¿ Escola Brasileira de Administração Pública e de Empresas, Fundação Getúlio Vargas, Rio de Janeiro, 2000. This paper analyses the effect of International capital flows and their behavior for emergent countries, focused in Brazilian financial market. It considers that capital flows had dramatically increased, however their impact, proposals on changes in international market and capital controls has not been clear. Considering capital flows In comparison to portfolio investments and to direct investments, this paper, also aims to discuss and highlight questions whether the concepts that capital flows generally associated to portfolio investments are frequently connected with incidence of crises meanwhile the second have been associated with growth in some countries.